Crime prevention-based society: Prevention in the 21st century (Academic Journal of Internal Affairs, 2020)
Due to new challenges resulted in globalisation technologies, the character of delinquency changed perfectly, new risk factors appeared on the area of criminality that we have to face now. What could be the solution? The here presented book tries to give an answer, which is – simply formulated – a society approach based on prophylaxis.
Keywords: crime prevention; globalisation technologies; criminality